Long-Acting Injectable Antipsychotics-A Review on Formulation and In Vitro Dissolution - Magdalena Markowicz-Piasecka; Marcin Kubisiak; Katarzyna Asendrych-Wicik; Michał Kołodziejczyk; Joanna Grzelińska; Małgorzata Fabijańska; Tomasz Pietrzak (MDPI AG, 2023)
Long-acting injectable (LAI) neuroleptics constitute an effective therapeutical alternative for individuals suffering from persistent mental illness. These injectable pharmaceuticals help patients manage their condition better and improve long-term outcomes by preventing relapses and improving compliance. This review aims to analyse the current formulation aspects of LAI neuroleptics, with particular emphasis on analysis of drug release profiles as a critical test to guarantee drug quality and relevant therapeutical activity. While there is no officially approved procedure for depot parenteral drug formulations, various dissolution tests which were developed by LAI manufacturers are described. In vitro dissolution tests also possess a critical function in the estimation of the in vivo performance of a drug formulation. For that reason, thorough inspection of the in vitro-in vivo correlation (IVIVC) is also discussed.